2018
DOI: 10.1002/ags3.12183
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and recurrence‐free survival in patients with hepatocellular carcinoma after achieving sustained virological response to interferon therapy for chronic hepatitis C

Abstract: AimSome patients who achieve a sustained virological response (SVR) to interferon (IFN) treatment for chronic hepatitis C prior to hepatic resection for hepatocellular carcinoma (HCC) experience postoperative recurrence. This study investigated the relationship between obesity and postoperative HCC recurrence in SVR patients.MethodsFifty‐nine patients who had achieved SVR before hepatic resection were evaluated. Patients had a solitary tumor ≤5 cm in diameter or ≤3 lesions each ≤3 cm in size with no macroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Our group and other researchers previously reported that obesity is associated with poor prognosis in HCC 25 – 27 . Thus, elevated BMI has been considered a predictive risk factor in several cancers, including HCC.…”
Section: Discussionsupporting
confidence: 55%
“…Our group and other researchers previously reported that obesity is associated with poor prognosis in HCC 25 – 27 . Thus, elevated BMI has been considered a predictive risk factor in several cancers, including HCC.…”
Section: Discussionsupporting
confidence: 55%
“…Liver steatosis and the metabolic syndrome per se are in close link with an increased risk of mortality as well as hepatic and extra‐hepatic malignancies . Furthermore, obesity was found to be an independent risk factor for HCC recurrence in patients who achieved SVR with interferon‐based regimens regardless of baseline liver fibrosis grade or the presence of cirrhosis . These previous findings, combined with our real‐life data regarding HCC occurrence in the DAA era, highlight the importance of LS as a major risk factor for poor outcome and warrant a special consideration of screening and follow‐up in this specific population.…”
Section: Discussionsupporting
confidence: 65%
“…3 To improve the survival of these patients, curative treatment for HCC is essential. Previous reports have demonstrated the possible favorable effect of SVR before hepatectomy on surgical outcomes [4][5][6][7][8][9][10] ; however, the true impact of SVR is not well-documented for various reasons.…”
Section: Introductionmentioning
confidence: 99%